2011
DOI: 10.1080/09658211.2011.613847
|View full text |Cite
|
Sign up to set email alerts
|

Odour-induced mental time travel into the past and future: Do odour cues retain a unique link to our distant past?

Abstract: Proustian memories, or memories spontaneously evoked by taste and odours, have been argued to be uniquely linked to our remote past. This view suggests an asymmetry between odour-cued memories and odour-cued representations of future events regarding their temporal distance to the present. We investigated the temporal distribution and other phenomenological qualities of autobiographical memories and future events employing a 2 (temporal direction: past vs future) × 3 (cue type: verbal, visual, and odour) mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 28 publications
7
36
1
Order By: Relevance
“…According to previous studies (e.g., Addis et al, 2007Addis et al, , 2009Anderson et al, 2012;D'Argembeau & Van der Linden, 2004;Miles & Berntsen, 2011;Rasmussen & Berntsen, 2014), we had no firm predictions whether voluntary past events would be faster to generate than voluntary future ones. Due to these inconclusive results concerning voluntary MTT and the lack of previous data on the retrieval dynamics of involuntary future representations, an interaction for the latency variable was not predicted.…”
Section: Hypothesesmentioning
confidence: 97%
See 3 more Smart Citations
“…According to previous studies (e.g., Addis et al, 2007Addis et al, , 2009Anderson et al, 2012;D'Argembeau & Van der Linden, 2004;Miles & Berntsen, 2011;Rasmussen & Berntsen, 2014), we had no firm predictions whether voluntary past events would be faster to generate than voluntary future ones. Due to these inconclusive results concerning voluntary MTT and the lack of previous data on the retrieval dynamics of involuntary future representations, an interaction for the latency variable was not predicted.…”
Section: Hypothesesmentioning
confidence: 97%
“…It is also reported that future MTT is more personally important to the self than past MTT (Addis, Wong & Schacter, 2008;Berntsen & Bohn, 2010). Finally, it has been demonstrated that future representations are temporally closer to the present than their mnemonic counterparts (Addis et al, 2008;Spreng & Levine, 2006; see also Berntsen & Jacobsen, 2008;Finnbogadόttir & Berntsen, 2011;Miles & Berntsen, 2011).…”
Section: Past and Future Episodic Thinking And The Concept Of Mttmentioning
confidence: 98%
See 2 more Smart Citations
“…Although Tulving originally used the term MTT to refer to mentally travelling to episodic (i.e., specific) events in the past or future (Tulving, 2002), studies have shown that individuals sometimes identify more general This is an Author's Accepted Manuscript of an article published in Nordic Psychology, 65:2, 137-165, available online at: http://www.tandfonline.com/10.1080/19012276.2013 events during MTT (e.g. Miles & Berntsen, 2011). Hence, we use the term MTT as referring to mentally travelling to both specific and general past and future events.…”
Section: This Is An Author's Accepted Manuscript Of An Article Publismentioning
confidence: 99%